2020
DOI: 10.1159/000510344
|View full text |Cite
|
Sign up to set email alerts
|

O-Arm Stereotactic Imaging in Deep Brain Stimulation Surgery Workflow: A Utility and Cost-Effectiveness Analysis

Abstract: <b><i>Introduction:</i></b> Deep brain stimulation (DBS) surgery is an established treatment for movement disorders. Advances in neuroimaging techniques have resulted in improved targeting accuracy that may improve clinical outcomes. This study aimed to evaluate the safety and feasibility of using the Medtronic O-arm device for the acquisition of intraoperative stereotactic imaging, targeting, and localization of DBS electrodes compared with standard stereotactic MRI or computed tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 46 publications
0
18
1
Order By: Relevance
“…Regarding side effects for the patient, the average DLP was 159 mGy cm, which is 5 times lower than recommendations (850 mGy cm) of the French Radioprotection and Nuclear Safety Institute (Institut de radioprotection et de sûreté nucléaire) for a single cerebral CT scan acquisition and in the lower range compared with various European recommendations. 26,27 The DLP we report is lower than…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Regarding side effects for the patient, the average DLP was 159 mGy cm, which is 5 times lower than recommendations (850 mGy cm) of the French Radioprotection and Nuclear Safety Institute (Institut de radioprotection et de sûreté nucléaire) for a single cerebral CT scan acquisition and in the lower range compared with various European recommendations. 26,27 The DLP we report is lower than…”
Section: Discussioncontrasting
confidence: 64%
“…26,27 The DLP we report is lower than in previous studies, ranging from 213 to 234 mGy cm, despite multiple acquisitions ensuring correct accuracy and localization (1 for robot calibration, 1 before drilling the skull, and another one before biopsy sampling). 28-30…”
Section: Discussionmentioning
confidence: 99%
“…Many factors in the surgical treatment play a corresponding role in the diagnosis and treatment of the disease, including the patients' condition, degree of cooperation, clinical experience, and general function status; the selection of the target during the surgery depends on clinical experience of the physicians [ 23 ]. Furlanetti et al [ 24 ] experimented with stereotaxic imaging to reduce the duration and cost of image acquisition without compromising accuracy. In this study, 37 patients (92.5%) in stereotactic surgery had an effect markedly effective.…”
Section: Discussionmentioning
confidence: 99%
“…Other methods to intraoperatively facilitate a three-dimensional depiction of the lead position are intraoperative CT or MRI [ 5 , 6 , 10 , 11 , 21 ]. Although these techniques have been shown to provide high accuracy of frameless stereotactic procedures, both modalities also require special equipment, which is a big investment for the most centers and hence not widely available [ 12 ]. This was also supported by the results of our survey, which revealed that intraoperative CT or MRI is not used in large-volume stereotactic centers in Germany.…”
Section: Discussionmentioning
confidence: 99%